The curricula of teacher training careers offered by public and private universities and their coherence with educational policies in Costa Rica - Chaves Salas, Ana Lupita (2023)
This article presents the result of an investigation whose purpose was to determine if the training plans for teachers of Preschool Education, Primary Education and some Secondary Education careers (Mathematics, Spanish, Sciences and English) of three public and three private universities are coherent with the Curricular Policy Educate for a new citizenship and the Educational Policy The Person: center of the educational process and transformative subject of society, approved by the Higher Education Council (CSE), in Costa Rica. The research was carried out in the period 2021-2022. A mixed study was carried out with a naturalistic and exploratory socio-critical approach that analyzed the proposal of the study plans of said universities to find, objectively, evidence in this regard, a questionnaire was also elaborated to meet the criteria of teachers and of those who coordinate these university careers, to which 77 of them responded. The results showed that the public universities included the reflective and critical analysis of both policies in the study plans of the Education careers and presented greater coherence with them than the private universities. Likewise, it was evidenced that the accredited careers are consistent with the policies and that both the coordinators of plans and the teaching staff of public and private universities knew about them and indicated that they are part of the study plans. Once the investigation was concluded, it was considered relevant to define guidelines so that the Ministry of Public Education (MEP), the highest employer, works jointly with public and private universities. Likewise, it is necessary to dialogue, integrate experiences and encourage a reflection that invites the redesign of the teacher training study plans based on the National Framework of Qualifications of Education careers in accordance with the exposed scenario and within the framework of university autonomy.